Implementasi Kurikulum Integratif Dalam Mempersiapkan Kader Ulama Berwawasan Global Di Madrasah Mu'allimin Mu'allimat Sunan Drajat Lamongan - Awwalul Fadlilah; Siti Mutholingah; Umi Salamah; Laila Nurdiana (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study investigates the implementation of an integrative curriculum at Madrasah Mu'allimin Mu'allimat Sunan Drajat Lamongan as a strategic effort to prepare globally minded ulama cadres. The research is grounded in the urgent need for Islamic education that not only deepens religious mastery (tafaqquh fid-dīn) but also equips learners with the global competencies required to navigate contemporary social, cultural, and technological dynamics. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. Data validity was ensured through source and method triangulation. The findings reveal three principal points. First, the integrative curriculum is structured by combining the salafiyah pesantren curriculum (75%) with the national Ministry of Religious Affairs curriculum (25%), framed by the maxim al-muḥāfaẓah ʿalā al-qadīm al-ṣāliḥ wa al-akhdhu bi al-jadīd al-aṣlaḥ. Second, curriculum implementation is operationalized through three integrated channels—intracurricular, cocurricular, and dormitory-based (keasramaan) activities—blending classical pesantren methods (bandongan, sorogan, halaqah) with modern pedagogical approaches. Third, graduate outcomes demonstrate balanced competence in classical Islamic sciences, mastery of kitab kuning, leadership, foreign-language proficiency, and responsiveness to contemporary issues. The study concludes that the integrative curriculum constitutes a strategic instrument for cultivating ulama who are simultaneously rooted in tradition and globally engaged.